Distinct oxytocin signaling pathways synergistically mediate rescue-like behavior in mice - Feng-Rui Zhang; Juan Liu; Jieqi Wen; Zi-Yan Zhang; Yijia Li; Eric Song; Li Hu; Zhou-Feng Chen (Proceedings of the National Academy of Sciences, 2025)
Spontaneous rescue behavior enhances the well-being and survival of social animals, yet the neural mechanisms underlying the recognition and response to conspecifics in need remain unclear. Here, we report that observer mice experience distress when encountering anesthetized conspecifics, prompting spontaneous rescue-like behavior toward the unconscious mice. This behavior facilitates the earlier awakening of anesthetized mice while simultaneously alleviating stress in the helper mice. Our findings reveal that endogenous oxytocin (OXT) release from the hypothalamic paraventricular nucleus (PVN) to the oxytocin receptor (OXTR) in the central nucleus of the amygdala (CeA) regulates the emotional component of rescue-like behavior. In contrast, OXT release from the PVN to OXTR in the dorsal bed nucleus of the stria terminalis (dBNST) mediates the motor component of the behavior. Furthermore, we demonstrate that these two pathways exhibited distinct temporal dynamics and functional roles. The OXT PVN -OXTR CeA pathway is activated in a transient and intense manner, acting as a trigger for rescue-like behavior, whereas the OXT PVN -OXTR dBNST pathway responds in a sustained manner, ensuring the continuation of the behavior. These findings highlight the remarkable ability of rodents to engage in targeted helping behavior and suggest that distinct subcortical oxytocinergic pathways selectively and synergistically regulate the motor and emotional aspects of rescue-like behavior.